Effect of hypertonic and isotonic saline on clinical, haematological, biochemical and electrocardiographic parameters in forestomach impaction in buffaloes - Saxena, Rakesh; Dua, K; Uppal, S K; Saini, N (The Indian Journal of Animal Sciences, 2007)
The present study was conducted to observe the effects of intravenous infusion of hypertonic and isotonic saline on haematobiochemical and electrocardiographic parameters in buffaloes suffering from forestomach impaction. Buffaloes (13) suffering from forestomach impaction were selected and divided into 2 groups. In group 1 (n=7), isotonic saline solution was given @ 20 ml/kg body weight whereas in the animals of group 2 (n= 6) hypertonic (7.5%) saline solution was given @ 2 ml/kg b.wt. as a constant infusion over a period of 2 h along with other symptomatic treatment. Following fluid therapy, a decrease in Hb and PCV values was observed in both the groups, indicating plasma volume expansion. There was an improvement in the plasma sodium and chloride concentrations. However, plasma potassium concentration showed a decreasing trend after fluid infusion in both the groups. The ECG showed a decrease in heart rate and an increase in PR interval in both the groups. Earlier clinical recovery was observed in the animals of group 2 indicating that hypertonic saline solution is effective in treatment of forestomach impaction along with other symptomatic treatment.